Synthesis and structure elucidation of novel pyrazolyl-2-pyrazolines obtained by the reaction of 3-(3-aryl-3-oxopropenyl)chromen-4-ones with phenylhydrazine - Santos, Clementina M.M. (2013)
Novel 3-aryl-5-{4-[5-(2-hydroxyphenyl)-1-phenylpyrazolyl]}-2-pyrazolines 2a-g have been prepared by the treatment of 3-(3-aryl-3-oxopropenyl)chromen-4-ones 1a-g with phenylhydrazine in refluxing acetic acid. NMR studies on deuteriochloroform solutions of pyrazolyl-2-pyrazolines 2a-g at different temperatures showed that at room temperature a mixture of diastereomers are present. This diastereoselectivity arises from the combination of the pyrazoline C-4 stereocenter and two planar chiral subunits due to internal steric hindrance. The energy barriers of this steric hindrance were overcome in DMSO-d6 solutions at 60oC. The acetylation of some pyrazolyl-2-pyrazoline derivativess 2a-c,e helped to confirm the presence of the referred mixture of diastereomers.